Design of the Space Camera Protection System during Launch Process - Siyu Wang; Haiying Tian; Changxiang Yan (International Journal of Aerospace Engineering)
In order to improve the safety and reliability and maintain the stability of imaging quality when a space camera with a cargo spaceship is launched, a protection system for the space camera is designed. Firstly, according to the mechanical properties of the space camera, a working principle of the protection system is elaborated, and a model of the system is proposed. Secondly, a protective cover and a vibration isolation block are designed on the basis of shape, size, and requirements of the space camera. Thirdly, based on the finite element mesh, static and sinusoidal vibration simulation calculations of the space camera and its protection system are carried out. Finally, the protection system is validated after mechanical experiment. The results reveal that the three directional fundamental frequencies of space camera are 43.39 Hz, 26.74 Hz, and 22.83 Hz, respectively, and the maximum response of sinusoidal vibration acceleration is 17.02 g, which is amplified by 3.4 times. The image quality of the space camera lens is consistent before and after the test, which satisfies the requirement of the cargo ship.